Health status and healthcare services utilisation among unaccompanied asylum-seeking minors settled in Switzerland: a protocol for a retrospective cohort study from a hospital-based youth outpatient clinic - Magdalini Patseadou; Dagmar M Haller; Catherine Chamay Weber (BMJ Open)
Introduction Unaccompanied asylum-seeking minors (UASMs) represent a population group with complex healthcare needs. Initial and ongoing healthcare is challenging for host countries but considered essential. This publication describes the protocol concerning a large cohort of UASMs settled in Switzerland in 2015–2016. Our aim is to assess their health status and examine their trajectories of healthcare services utilisation during the 3-year period after their initial health control.Methods and analysis We will retrospectively analyse data of all newly arrived UASMs aged 12–18 years who benefited from a first health assessment at the Youth Clinic of Geneva University Hospitals between 1 January 2015 and 31 December 2016. Source of data will be electronic medical records. Main outcomes include the determination of their health status (acute and chronic conditions) and the utilisation of different care sectors (ambulatory primary care and subspecialty clinics, emergency room and inpatient wards). A secondary outcome will be the identification of patients at risk for high use of services as well as those with limited access to care. We will extract the following data: demographic characteristics (age, gender and country of origin), social determinants (place of residence, the presence of family in Geneva, school performance and asylum status), clinical information (reason for attending service, anthropometric measurements and medical diagnosis at discharge) and laboratory parameters (complete blood count, ferritin level, 25-hydroxyvitamin D level, hepatitis B antigen and antibodies, tetanus antibodies, QuantiFERON and stool and serology tests for intestinal parasites). We will collect data from first health assessment and during a follow-up period of 3 years for each patient.Ethics and dissemination In accordance with the Swiss clinical research law, this protocol has been approved by the local ethics committee (project ID: 2021–01260). Our findings will provide important information for the development of quality healthcare services focusing to UASMs. We intend to disseminate our results through publication in peer-reviewed journals.